Laser performances of passively Q-switched Pr3+-doped oxide lasers based on Pr3+, Mg2+:SrAl12O19 crystal and Co:ASL saturable absorber. (July 2021) - Zhang, Teng; Zhou, Lunbin; Zou, Jingyu; Bu, Yikun; Xu, Bin; Xu, Xiaodong; Xu, Jun
Highlights: Diode-pumped CW Pr, Mg:SRA lasers at 643 nm, 724 nm and 622 nm are demonstrated. The highest output power of the diode-pumped Pr, Mg:SRA laser is 675 mW. Passively Q-switched Pr, Mg:SRA lasers are also demonstrated, for the first time. The shortest pulse width is 105.6 ns for the 622 nm laser, while 211.7 ns for the 643 nm laser. Abstract: We report on compact blue-diode-pumped Pr, Mg:SrAl12 O19 (SRA) lasers in continuous-wave and passively Q-switched regimes. For continuous-wave mode, three lasers have been achieved with maximum output powers of 675 mW, 566 mW and 312 mW at wavelengths of 643 nm, 724 nm and 622 nm, respectively. The maximum slope efficiencies with respect to absorbed power for the three lasers are 18.7%, 16.6% and 11.1%. Using a uniaxial Co 2+ -doped strontium, lanthanum and magnesium aluminate (Co:ASL) crystal as saturable absorber with remarkable absorptions at 643 nm and 622 nm, we have achieved passively Q-switched Pr, Mg:SRA lasers at the two emissions with maximum output powers of 175 mW and 118 mW, respectively, for the first time to our knowledge. The shortest pulse widths for the two lasers are 211.7 ns and 105.6 ns. Correspondingly, we estimated that pulse energies and peak power are 2.13 μJ and 10.1 W for the 643 nm laser as well as 0.98 μJ and 9.27 W for the 622 nm laser. This work reveals that Pr, Mg:SRA as one of the few reported Pr 3+ -doped oxides could be potential in generating compact and efficient lasers in visible spectral range.